Ultrasound Imaging of the Thoracic Epidural Space. Issue 2 (1st March 2002) - Grau, T.; Leipold, R. W.; Delorme, S.; Martin, E.; Motsch, J.
Abstract : Background and Objectives: In thoracic epidural anesthesia, the "loss of resistance" technique is the standard technique for the identification of the epidural space (EDS), the feedback to the operator is often solely tactile. Our aim was to establish ultrasonography for the prepuncture demonstration of the anatomic structures surrounding the thoracic EDS and to evaluate its precision and imaging quality. Methods: We examined 20 volunteers. In each participant, the extradural space and the neighboring anatomic landmarks in the intervertebral space Th 5-6 were identified using 2 imaging techniques: magnetic resonance imaging (MRI) and ultrasonography. We compared corresponding images regarding distance measurements and the visibility of anatomic landmarks. Results: The capacity of ultrasound imaging (US) to depict the thoracic EDS was limited. Due to the better overview, MR images were easier to interpret. However, US proved to be of better value than MRI in the depiction of the dura mater. All important landmarks for the puncture of the thoracic EDS could be identified with both techniques. The overall correlation was satisfactory. US depicted the different structures of the thoracic EDS with an acceptable precision (confidence interval, 4.6 to 8.7 mm). Conclusions: US showed good correlation with MRI, which is a standard imaging technique for the depiction of the spine. We anticipate that prepuncture ultrasonography may facilitate thoracic epidural anesthesia by needle placement.